Control mechanisms on the reactive silicate fluxes by using on board resuspension experiments in the eutrophicated coastal environment - Özkan Ebru Y.; Buyukisik Hasan B. (Oceanological and Hydrobiological Studies)
This study aims to differentiate bio-mediated and biogenic CO3-2 precipitation or terrestrial CO3-2 input using onboard incubation techniques, to investigate the effects of resuspension in the coastal environment and to increase our understanding of predicted relationships between silicate releases and other biogeochemical variables in resuspension events. Relationships between dark silicate flux and BSi, CO3-2, OrgC, Mn (manganese) according to the seasons were examined. The silica flux is controlled by the CaCO3 coating on the diatom skeletons due to the fact that diatom skeletons act as crystallization nuclei in the calcite precipitation that is biologically affected. The reduction in flux with BSi may be due to the reduction in the surface areas of larger diatom species. The negative linear relationships observed between silica fluxes and CO3-2 is indicative of RSi fluxes constrained by bio-mediated carbonate increase. Linear relationships which are the same in their slopes but differ in their intercepts, reveal the effect of the change in diatom size on silica flux. Smaller diatoms have more surface area per unit volume, meaning an increased silica flux. On the other hand, seeing different CO3-2 values at stations with the same orgC value have increased the confidence interval (CI) 95% in the linear relationship. The presence of different silica flux values in stations with the same carbonate value may be explained both by different orgC values and by diatoms containing different group sizes. The silica flux is controlled by the CaCO3 coating on the diatom skeletons due to the fact that diatom skeletons act as crystallization nuclei in the calcite precipitation that is biologically affected. The main mechanism controlling the reactive silica flux is carbonate precipitation. The observation of different silica flux values in stations with the same carbonate values can also be explained by OrgC.